DEFINING TERRITORIAL BEHAVIOUR AT KAMPUNG’S TRANSITIONAL SPACE - Fitria, Tika Ainunnisa; Firdaus, Rohana (Vitruvian : Jurnal Arsitektur, Bangunan dan Lingkungan, 2025)
Yogyakarta’s urban neighborhood, called kampung, encompasses the neighbouring life, shown in its transitional space. Territoriality in the context of kampung cannot be separated from the social ties between its residents, which builds familiarity. The leeway of transitional space use shows the specific behavior of Kampung’s residents towards territorial. Residents have their concepts in interpreting transitional space. There are different interpretations of territory and its significance. However, previous studies have not defined territorial behavior in the kampung context. This study was conducted qualitatively, located in two kampungs, Notoyudan and Prawirotaman. They have significant differences in terms of environmental typology and community background. This study focuses on defining territorial behavior in kampung through 1) a review of literature relating to territorial behavior by Altman (1976); 2) observing territorial phenomena; and 3) resuming the results toward the theory of territorial behavior. This research concludes that territorial behavior can be defined as a territorial transaction as a form of a resident’s social existence in the neighborhood. Territorial behavior becomes a spatial setting, reducing social disparities among Kampung’s residents. This behavior will continue, providing that transitional space still exist. This finding enriches the definition of territorial behavior and contributes to the theory of architecture behavior.